Curriculum Evaluation of the Bachelor of Education Program in Cham of Rajabhat Maha Sarakham University 2005 Revised 2006 - ฤทธิเดช สมบัติ; พูลพุทธา อพันตรี (Journal for Developing the Social and Community, 2016)
The research aimed to evaluate the curriculum of the Bachelor of Education Program in Cham of Rajabjat Maha Sarakham University 2005 revised in 2006 focusing on curriculum contents and products. The samples were university students, graduates and assistant teachers. They were selected by the stratified random sampling method. The instrument was a questionnaire. The statistics used were percentage, mean and standard deviation. Results of the research are as follows: (1) the overall opinion of the research findings showed that the overall opinion of the university students on the curriculum contents was at a high level. (2) Regarding the assessment of primary factors, the overall opinion of the university students and graduates on the primary factors was at a high level. (3) Regarding the evaluation of curriculum process, the overall opinion of the university students and graduates on the curriculum process was at a high level. (4) The overall opinion of the assistant teachers toward the required intern students was at a high level.